Normothermic Cardiopulmonary Bypass with Beating Heart for Management of Renal Cell Carcinoma with Atrial Tumor Thrombus. Issue 4 (June 2013) - Calcaterra, Domenico; Collins, Thomas E.; Turek, Joseph W.; Parekh, Kalpaj R.; Bashir, Mohammad; Ueda, Kenichi; Hanada, Satoshi; Brown, James A.
Renal cell carcinoma is occasionally complicated by the formation of a neoplastic thrombus invading the inferior vena cava. Rarely, the thrombus extends into the vena cava, reaching the right atrium. In these situations, despite the advanced tumor stage, surgical resection continues to offer the best chance for effective treatment. The operation requires a complex surgical approach with mobilization of the liver and use, in most cases, of extracorporeal circulation, which allows removal of the tumor thrombus from the right atrium. Traditionally, the intervention is performed using deep hypo-thermic circulatory arrest or, less frequently, using moderate hypothermia, aortic cross clamping, and cardioplegic cardiac arrest. These strategies have the downside of causing increased blood loss, coagulopathy, and long operative time and can potentially have a negative impact on survival. We report a different operative approach using normothermic cardiopulmonary bypass, with the expectation of lowering the rate of blood product transfusions, hospital length of stay, and overall incidence of complications.